PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK MATERI BENTUK-BENTUK GEOMETRI BERBASIS SAINTIFIK ANAK KELOMPOK B DI TAMAN KANAK-KANAK - Umiyati Umiyati; Syafdaningsih syafar; sri sumarni (Tumbuh Kembang: Kajian Teori dan Pembelajaran PAUD, 2019)
This study aims to produce Student Worksheets (LKPD) Development Of Work Sheets Of Participants In The Material Of Geometry Forms Based On Saintifices In Group B Children In Kindergarten which are valid and practical. Development is carried out using the Rowntree model, namely planning, development, evaluation. Evaluations carried out using Tessmer formative evaluation methods include self evaluation, expert review, one to one evaluation and small group evaluation. Data analysis from expert review obtained an average percentage of 94.5% with very valid categories which included the validity of content, constructs and media. This means that the LKPD is already in content, which is in accordance with the material for children in group B, including connecting one object with other objects in the same shape. Then the construct includes a scientific approach and assessment in accordance with the characteristics of child development. While the media can be seen from the completeness of the elements in the LKPD, images, writing and appearance. In the one to one evaluation and small group evaluation and product stages the average percentage was 96.2% with a very practical category. This means that LKPD is easy to implement, easy to check and the costs used are not too high. In order to achieve a valid and practical LKPD perfection, there is still a recognized lack of 5.5%. In material matters, namely the lack of use of the trapezoidal shape and parallelogram, the material is dominated by square, rectangular and circular shapes. The lack of media is that there are some words that are not familiar to children in group B, for example the scientific word. Whereas practically there is still a deficiency of 3.8%, namely the high cost of design. For this reason, further research is recommended to develop parallelogram and trapezoidal material and simple designs.